Spectrum subtraction method for simultaneous determination of acetaminophen and caffeine in panadol extra dosage forms - Sebaiy, Mahmoud Mohammed; Mattar, Amr Abd El-Hakeem (European Journal of Chemistry, 2020)
A simple, specific, accurate and precise spectrophotometric method was established for simultaneous determination of acetaminophen and caffeine in pure form and in their pharmaceutical formulation commercially known as Panadol Extra®. Spectrum subtraction has been used in simultaneous determination of both drugs without prior separation. Spectrum subtraction method parameters were validated according to ICH guidelines in which accuracy, precision, repeatability and robustness were found in accepted limits (98-102%). The linearity range was 7.5-45 µg/mL for caffeine and 4-22 µg/mL for acetaminophen with correlation coefficients ≥0.9990 for both drugs. Advantages and disadvantages of spectrum subtraction were discussed and statistical comparison between the proposed method and the reference one was performed.